STRATEGI KOMUNIKASI KANTOR PELAYANAN PAJAK PRATAMA PEKANBARU TAMPAN DALAM MENINGKATKAN KESADARAN WAJIB PAJAK DI PEKANBARU MELALUI SISTEM LAYANAN PAJAK ONLINE E-BILLING - Romi, Kurnia; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The number of taxpayers increased every year, but it is not followed by an awareness of the taxpayer to report his taxes, so that the Directorate General of Tax policy making online tax service system E-Billing to simplify the tax filing process. This study aims to determine the role of communicator, assessment destination communication message, media utilization, as well as the introduction of target audiences communication by the Tax Office Pratama Pekanbaru Tampan in raising awareness of the taxpayer through online tax service system E-Billing.The research sites is at Tax Office Pratama Pekanbaru Tampan on MR.SM.Amin Street (Ring Road Arengka II). The subject is determined by purposive technique that consists of the Head of extensification, Staff Extensification, and 3 taxpayer. Data collection techniques include interviews, observation and documentation.The results of this study indicate that the strategy of KPP Pekanbaru Tampan in increasing awareness Taxpayers throught socialization of online tax service system E-Billing. The first is to determine the communicator has the credibility and understanding of E-Billing and able to deliver messages communicatively. The second is planning message processing that includes a persuasive, educative and informative messages. The third is using communication media such as face-to-face media, print media, electronic media and internet media. Fourth, audience target consists of the taxpayer and the public.Keywords: Communication Strategy, Awareness Taxpayer, E-Billing